Peran Modal Sosial Masyarakat Penambang Emas dalam Mempertahankan Tambang Ilegal di Taman Hutan Raya Sulawesi Tengah (The Role of Social Capital of Gold Miners on Defending Illegal Mining in Central Sulawesi Forest Park) - Amelia, Nur Rizky; Kartodihardjo, Hariadi; Sundawati, Leti (Jurnal Sylva Lestari, 2019)
The approval of mining permits in the area of the Central Sulawesi Forest Park to a private company caused the emerging of illegal mining by the local community. This study aims to identify the characteristics and social capital of local community miners and their role in the conflict and community resistance. This is explorative research using a qualitative approach. Data was collected through a structured interview to 30 miners as respondents and in-depth interviews with various related stakeholders such as tribal leaders and local government. The results showed that although the social capital of the local community miners was relatively moderate, it could encourage community resistance to the government's efforts to close the illegal mining. The results were affected by a common knowledge that mining is the only source of income for the community. Also, the support of tribal leaders and village officers became a symbolic power that could propel the collective actions of the local community miners. Keywords: forest park, illegal gold mining, social capital, conflict, collective action